Indigenous resistance in western Paraná: the search for the recognition of the Tekora Guasu Guavirá indigenous territory in municipalities of Guaíra end Terra Roxa (Research, Society and Development, 2022)
The existence of Avá-Guarani community in western Paraná is the product at long process of resistance to the colonization of the Brazilian border and to public urbanization policies. However, the recent process of indigenous reoccupation generated reactions from producers linked to agribusiness, causing the establishment of social conflict that produced violence, hostility and disrespect for the Guaranis. Through bibliographic and documentary research and using the dialectical method, the present study aimed to analyze the historicity of the struggle and resistance process of that community, as well as the bases of the conflict. In addition, we sought to include aspects related to the judicialization of the conflict and the legal discussions about theory of indigenato and theory of time frame.